Psychometric Evaluation and Validation of the Questionnaire on Stress in Diabetic Patients in Brazilian Portuguese (Global Journal of Medical Research, 2025)
Introduction: Diabetes mellitus (DM) is the most common chronic metabolic disease worldwide, affecting individuals of all ages. Objective: To analyse the psychometric properties of the Brazilian version of the Questionnaire on Stress in Diabetic Patients– Revised (QSD-R). Methods: A cross-sectional methodological study was conducted at both public and private healthcare services involving 315 patients diagnosed with type 2 diabetes. Construct validity was evaluated through exploratory and confirmatory factor analysis. Reliability was estimated using Cronbach’s alpha coefficient and the intraclass correlation coefficient (ICC). Convergent validity was tested with the Diabetes-21 Quality of Life Scale and the Hospital Anxiety and Depression Scale (HADS).